Interferon γ and plasminogen activator inhibitor 1 regulate adhesion formation after partial hepatectomy. Issue 4 (March 2014) - Ohashi, K.; Yoshimoto, T.; Kosaka, H.; Hirano, T.; Iimuro, Y.; Nakanishi, K.; Fujimoto, J.
<x xml:space="preserve">Abstract</x> Background The pathophysiology of intra‐abdominal adhesions has not been studied extensively. The aim of this study was to elucidate the molecular mechanisms underlying adhesion formation in a murine model and in patients undergoing hepatectomy. Methods Partial hepatectomy was performed using bipolar forceps in mice. Wild‐type mice, antibodies to CD4 and interferon (IFN) γ, IFN‐γ, natural killer T (NKT) cells and plasminogen activator inhibitor (PAI) 1 knockout (KO) mice were used. Recombinant hepatocyte growth factor (HGF) was tested for its ability to prevent adhesions. Liver specimens were obtained during surgery from patients undergoing hepatectomy. Adhesion formation was evaluated using a scoring system that ranged from 0 (no adhesions) to 5 (severe adhesions). Levels of IFN‐γ and PAI‐1 mRNA, and protein concentration of PAI‐I were measured, and fluorescence immunostaining was performed. Results Adhesion formation depended on IFN‐γ produced by NKT cells, and NKT KO mice developed few adhesions (mean(s.d.) 1·7(0·3) versus 4·6(0·4) in wild‐type mice; P = 0·037). In wild‐type mice, the level of PAI‐1 mRNA increased after hepatectomy, followed by a decrease in the tissue plasminogen activator (tPA) mRNA level. Adhesion formation was inhibited completely in PAI‐1 KO mice (0(0) versus 4·1(0·8) in wild‐type mice; P = 0·002). HGF inhibited formation of abdominal adhesions after hepatectomy by reducing IFN‐γ and PAI‐1 levels, and increasing tPA levels compared with those in mice treated with phosphate‐buffered saline (P < 0·001, P = 0·002 and P = 0·035 respectively). In human liver specimens, NKT cells accumulated in the liver after hepatectomy, and PAI‐1 expression was increased 5·25‐fold (P = 0·030). Conclusion IFN‐γ is a key molecule for abdominal adhesion formation after hepatectomy, acting via the reciprocal balance of PAI‐1 and tPA. This molecular mechanism may also regulate adhesion formation in patients following hepatectomy. HGF inhibited formation of adhesions by regulating IFN‐γ and PAI‐1, suggesting that it may be an important target for prevention of adhesions after hepatectomy. <boxed-text content-type="box" id="bjs9405-blkfxd-0001" position="anchor" orientation="portrait"> Surgical relevance Postoperative intra‐abdominal adhesions can be asymptomatic or cause significant morbidity and mortality. Adhesion formation after hepatectomy has not been studied extensively. In the present study, the molecular mechanisms underlying intra‐abdominal adhesions after hepatectomy were investigated in a murine model and in patients. Interferon (IFN) γ produced by natural killer T cells is a key molecule for adhesion formation after hepatectomy in mice, acting via the reciprocal balance between plasminogen activator inhibitor (PAI) 1 and tissue plasminogen activator, the pivotal factors in fibrinolytic activity. This mechanism was also involved in the regulation of adhesions in human tissue samples. Hepatocyte growth factor (HGF) strongly inhibited adhesion formation by regulating IFN‐γ and PAI‐1. These results indicate that IFN‐γ and PAI‐1 are possible therapeutic targets, and HGF could prevent postoperative adhesion formation after hepatectomy. </boxed-text>